The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.2136/vzj2014.06.0060
|View full text |Cite
|
Sign up to set email alerts
|

Spatial‐Scale Prediction of the SVAT Soil Hydraulic Variables Characterizing Stratified Soils on the Tibetan Plateau from an EnKF Analysis of SAR Soil Moisture

Abstract: In highly stratified soils as on the Tibetan Plateau, uncertainty associated with a vertical profile of soil and hydraulic properties largely restricts the performance of Soil Vegetation Atmosphere Transfer (SVAT) model. In lieu of commonly used pedotransfer functions (PTFs) or artificial neural networks (ANNs), soil hydraulic properties in this study were inverted from an Ensemble Kalman filter (EnKF) analysis of Synthetic Aperture Radar (SAR) surface soil moisture. The calibrated SVAT scheme using inverted s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 85 publications
0
13
0
Order By: Relevance
“…For the estimation of dielectric constant, both satellite retrievals and models require a similar type of soil property information. For example, if the clay fraction in soil maps used for both land surface model and satellite retrievals is overestimated [5,46], then this is escalated to the overestimation of wilting point or field capacity in the land surface models and adversely affects the satellite retrievals to convert dielectric constant to soil moisture, resulting in the similar overestimation of soil moisture in both satellite retrieval and land surface models [18,47,48].…”
Section: Triple Collocation (Tc) Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the estimation of dielectric constant, both satellite retrievals and models require a similar type of soil property information. For example, if the clay fraction in soil maps used for both land surface model and satellite retrievals is overestimated [5,46], then this is escalated to the overestimation of wilting point or field capacity in the land surface models and adversely affects the satellite retrievals to convert dielectric constant to soil moisture, resulting in the similar overestimation of soil moisture in both satellite retrieval and land surface models [18,47,48].…”
Section: Triple Collocation (Tc) Methodsmentioning
confidence: 99%
“…There are two different approaches in retrieval ensembles: (1) the deterministic approach to assemble multiple retrieval models [63]; and (2) the probabilistic approach to process various retrieval input data with the same retrieval algorithm, where the input errors are stochastically defined in a form of PDF (Probability Density Function) [48,52,64]. These are also called PDF methods.…”
Section: The Concept and Type Of Retrieval Ensemblesmentioning
confidence: 99%
“…Pauwels et al (2009) were one of the first to optimize soil hydraulic parameters of a land surface model by data assimilation, assimilating synthetic aperture radar data. Lee (2014) used synthetic aperture radar soil moisture data to estimate soil hydraulic properties at the Tibetan plateau using the EnKF and a soil-vegetationatmosphere transfer model. Bateni and Entekhabi (2012) assimilated land surface temperature with an ensemble Kalman smoother and achieved a better estimate of the partitioning of energy between sensible and latent heat fluxes.…”
Section: Introductionmentioning
confidence: 99%
“…It was previously shown that the DEnKF performs better with a reduced ensemble size and converges better than the standard EnKF [23], [31]. For ensemble generation, please see [23], [24]. A SVAT model propagated soil moisture ensembles for 40 days.…”
Section: ) Sequential Ensemble Kf (Denkf)mentioning
confidence: 99%